2017
DOI: 10.5433/1679-0359.2017v38n4supl1p2619
|View full text |Cite
|
Sign up to set email alerts
|

Performance and nutritional parameters of lactating cows on pasture receiving castor bean meal

Abstract: This study aimed to evaluate the inclusion of castor bean meal in the diet for lactating cows on Bracharia brizhanta pasture and its implications for nutritional and productive parameters. Eight crossbred cows were distributed in two 4 x 4 Latin squares, with four (0%; 3.33%; 6.66% and 10%) inclusion levels of castor bean meal in the total diet. The experiment consisted of four experimental periods of 21 days each. The digestibility and dry matter intake were estimated from fecal output, checked with the aid o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 2 publications
0
2
0
Order By: Relevance
“…The time devoted to grazing by the animals in this study was considered normal for cattle (Boval and Sauvant, 2021). de Souza et al (2017) also reported no effects of replacing soybean meal with DCM on the grazing or rumination times of dairy cows. The trough time probably decreased due to the neutral detergent fiber content in the diet.…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…The time devoted to grazing by the animals in this study was considered normal for cattle (Boval and Sauvant, 2021). de Souza et al (2017) also reported no effects of replacing soybean meal with DCM on the grazing or rumination times of dairy cows. The trough time probably decreased due to the neutral detergent fiber content in the diet.…”
Section: Discussionmentioning
confidence: 63%
“…Nevertheless, as stated by Sampaio et al (2009), when the CP content is greater than 10%, the NDF substrate is used with greater efficiency. It is also noteworthy that, due to rumen fill, the substrate did not compromise total DM intake (Delevatti et al, 2019), which was 18% higher than the 4.8 kg d -1 estimated by the equation of BR-CORTE (2016). De Souza et al (2017 also did not observe differences in CP intake or digestibility in cows that received supplement with DCM replacing soybean meal while on U. brizantha pasture.…”
Section: Discussionmentioning
confidence: 70%